IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING DI MIN 3 TANGERANG - Ika Ika; Rasban Yoyon; Ega Permata Dewi (PMPP Lembaga Penelitian dan Studi Kebijakan, 2022)
Blended Learning is a learning approach that integrates traditional face-to-face learning and distance learning using Online learning resources. Based on research of educationists by comparing learning outcomes between face to face, combination (Blended Learning), and the Internet (Online Learning) obtained data that the use of combination methods (Blended Learning) is more effective in improving student learning outcomes. Blended Learning in distance education programs is deemed necessary to strengthen the subject matter that has been obtained and studied by students online, besides combining Online and face-to- face learning methods using Blended Learning can also shape the social environment of students in order to communicate, interact , and build relationships directly with other students. In this research, researchers took 4 aspects of learning to be used as research focus, namely: 1) Planning ,; 2) Implementation; 3) Evaluation; 4) and inhibiting factors and supporting factors for the implementation of Blended Learning in Madrasah Ibtidaiyah Negeri 3 Tangerang